การเสริมสร้างสมรรถนะการให้คำปรึกษาของนักเรียนเพื่อนที่ปรึกษา โดยการฝึกอบรมเชิงจิตวิทยา - แสงทอง นพพร; ศรีสวัสดิ์ พัชราภรณ์; วรเจริญศรี สกล (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2021)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสมรรถนะการให้คำปรึกษาของนักเรียนเพื่อนที่ปรึกษา 2) ศึกษาผลของการเสริมสร้างสมรรถนะการให้คำปรึกษาของนักเรียนเพื่อนที่ปรึกษา โดยการฝึกอบรมเชิงจิตวิทยา การวิจัยแบ่งออกเป็น 2 ระยะ คือ ระยะที่ 1 ศึกษาสมรรถนะการให้คำปรึกษา กลุ่มตัวอย่างแบ่งเป็น กลุ่มผู้ให้ข้อมูล เป็นผู้เชี่ยวชาญกิจกรรมนักเรียนเพื่อนที่ปรึกษา จำนวน 22 คน และกลุ่มที่ใช้ศึกษาเป็นนักเรียนเพื่อนที่ปรึกษาที่โรงเรียนดำเนินกิจกรรมไม่ต่ำกว่า 3 ปี จำนวน 92 คน โดยสุ่มอย่างง่าย ระยะที่ 2 เสริมสร้างสมรรถนะการให้คำปรึกษา ผู้วิจัยเลือกแบบเจาะจงจากนักเรียนในระยะที่ 1 ที่มีคะแนนตั้งแต่เปอร์เซ็นไทล์ที่ 25 ลงมา จำนวน 24 คน แบ่งเป็นกลุ่มทดลองและควบคุม กลุ่มละ 12 คน โดยสุ่มอย่างง่าย เครื่องมือที่ใช้ในการวิจัย ได้แก่ 1) แบบสัมภาษณ์สมรรถนะการให้คำปรึกษา 2) แบบวัดสมรรถนะการให้คำปรึกษา 3) โปรแกรมการฝึกอบรมเชิงจิตวิทยาเพื่อเสริมสร้างสมรรถนะการให้คำปรึกษา สถิติที่ใช้ ได้แก่ ค่าร้อยละ ส่วนเบี่ยงเบนมาตรฐานและค่า t ของกลุ่มตัวอย่างที่เป็นอิสระและไม่เป็นอิสระต่อกัน ผลการวิจัยพบว่า 1) สมรรถนะการให้คำปรึกษาของนักเรียนเพื่อนที่ปรึกษา มี 3 องค์ประกอบ ได้แก่ ความรู้ เจตคติและทักษะการให้คำปรึกษา และนักเรียนเพื่อนที่ปรึกษามีสมรรถนะการให้คำปรึกษาอยู่ในระดับมาก 2) การเสริมสร้างสมรรถนะการให้คำปรึกษาของนักเรียนเพื่อนที่ปรึกษา โดยการฝึกอบรมเชิงจิตวิทยา พบว่า 2.1) หลังทดลองของกลุ่มทดลอง มีสมรรถนะการให้คำปรึกษาสูงกว่าก่อนทดลองอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 2.2) หลังทดลอง กลุ่มทดลองมีสมรรถนะการให้คำปรึกษาสูงกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 คำสำคัญ: เพื่อนที่ปรึกษา; สมรรถนะการให้คำปรึกษา; การฝึกอบรมเชิงจิตวิทยา ABSTRACT This study aims (1) to examine the counseling competencies of peer counselors; (2) the effects of the enhancement of counseling competencies for peer counselors through psychological training. The subjects in this study were peer counselors with three years of experience and from the Secondary Educational Service Area One, Zone One in Bangkok. The study was divided into two phases. The first phase studied the counseling competencies of peer counselors. The sample was separated into counseling competencies information provider by interviewing structure with twenty-two professional counselors and 92 peer counselors studying counseling competencies. The second phase was the enhancement of counseling competencies for peer counselors through psychological training. The sample was selected by purposive sampling, and consisted of 24 peer counselors whose counseling competencies scores were lower than the 25th percentile and voluntarily participated in the psychological training. The research instruments were structured interviews, counseling competencies questionnaires and a psychology training program. The data were analyzed by mean, percentage and standard deviation, paired–sample t-test and an independent –samples t-test. The results of the study were as follows: 1) Regarding the study of peer counseling competencies, the results verified that there were three components contributing to the counseling competencies; counseling knowledge, attitudes towards counseling and counseling skills. The total and each components of counseling competencies were at a high level. 2) The effectiveness of psychology training in enhancing the counseling competencies were as follows: 2.1) The experimental group participated in the psychological training for enhancing counseling competencies and were significantly higher than before participating at a level of .05 2.2) The counseling competencies of the experimental group after participation was higher than the control group at a statistically significant level of .05 Keywords: Peer counselor; Competency; Psychological training